(untitled) (Eurasian Journal of Ecology, 2022)
The problem of the frequent occurrence of pathology of the gastrointestinal tract in the modern world is due to the high prevalence among almost all population groups. According to WHO forecasts, it is this type of disease that is a universal human disease of the 21st century, which in turn is directly related to people’s lifestyle, the amount of stress, the presence of any bad habits, the consumption of low-quality food, and environmental pollution. In this article, the interactions of miRNA and mRNA of target genes, which are involved in the development of oncological and borderline diseases of the gastrointestinal tract, have been studied, the binding sites of miRNA and mRNA of target genes have been identified. The characteristics of miRNA interactions with associated genes were determined. Bio- informatic calculation of gene and miRNA binding characteristics was performed using the MirTarget program. As a result of the data obtained, databases of genes and miRNAs involved in the pathogenesis of the gastrointestinal tract were created. Associative links between genes and miRNAs responsible for the development of oncological and borderline diseases of the gastrointestinal tract have been revealed. The genes responsible for the development of both types of groups of diseases, the expression of which is impaired both in oncological and borderline diseases of the gastrointestinal tract, have been identified. Key words: gastrointestinal cancer, borderline gastrointestinal diseases, miRNA, mRNA, target gene.